REVENUE MANAGEMENT MODEL BASED ON CAPACITY SHARING AND OVERBOOKING IN THE AIRLINE - Dewi, Oki Anita Candra (JEMIS (Journal of Engineering & Management in Industrial System), 2018)
Aviation industry often faced uncertainty demand and high level of cancellation. Revenue management in the airline is related to demand management policies to classify and estimate the various requests of pricing and capacity control. This study will develop airline revenue management model integrates luggage passengers with air cargo based on the control of air cargo space. The airline must pay attention to customer behavior due to high cancellation and no-show. In this case we deal with the aspect of the overbooking in which one of the ways to reduce the cost of spoilage due to cancellation or no show. Moreover, in this proposed model, we discuss the expected revenue function to maximize the expected revenue from the policies of accept or reject the booking requests between passengers and air cargo by the same airline. This study aims to develop expected revenue in the dynamic programming model in order to maximize the revenue expectations of the policy of accepting and rejecting booking request between passengers with air cargo in the same airline.